Antcin A, a phytosterol regulates SARS‐CoV‐2 spike protein‐mediated metabolic alteration in THP‐1 cells explored by the 1H‐NMR‐based metabolomics approach - Dakpa, Gyaltsen; Senthil Kumar, Kanthasamy Jayabal; Tsao, Nai‐Wen; Wang, Sheng‐Yang (Phytotherapy research, 2023)
The mechanism of SARS‐CoV‐2 spike protein‐mediated perturbations of metabolic pathways and modulation of antcin A, a steroid‐like compound isolated from Taiwanofungus camphoratus, are not studied. Here, we investigated the metabolic alteration by SARS‐CoV‐2 spike protein and the regulatory effect of antcin A on SARS‐CoV‐2 spike protein‐induced metabolic changes in the Phorbol 12‐myristate 13‐acetate (PMA)‐induced human monocytes (THP‐1) using proton nuclear magnetic resonance (1H‐NMR) and MetaboAnalyst 5.0 software. The cytotoxic potential of SARS‐CoV‐2 spike protein, antcin A, and dexamethasone was assessed by MTT assay. The metabolomic perturbations and their relation to human coronaviruses' receptors were evaluated by qPCR. This study indicated that the altered metabolites mediated by SARS‐CoV‐2 protein, such as methionine, phosphoenolpyruvic acid, canadine, glutamine, ethanolamine, and phenylalanine, were significantly reversed by antcin A. In addition, antcin A significantly inhibited SARS‐CoV‐2 spike protein‐mediated up‐regulation of TLR‐4 and ACE2 receptors, while GRP78 inhibition was not statistically significant. This is the first study to use 1H‐NMR to investigate SARS‐CoV‐2 spike protein‐induced metabolomic changes in PMA‐induced THP‐1 cells. Antcin A significantly reversed metabolomic alters while dexamethasone failed to fix them. Therefore, we believe that antcin A could be a potential candidate for therapeutic agents for viral infections related to a metabolic abnormality.